M6A RNA methylation contributes to translational control in heart failure progression. (25th November 2020) - Buchholz, E; Berulava, T; Elerdashvili, V; Pena, T; Lbik, D; Mohamed, B.A; Bohnsack, K.E; Bohnsack, M.T; Hasenfuss, G; Fischer, A; Toischer, K
Abstract: Background/Introduction: Heart failure, characterized by reduced cardiac function and left ventricular dilatation, is a leading cause of hospital admission and mortality. Among increased apoptosis and fibrosis, the progression of heart failure is accompanied by changes in gene expression. There is increasing evidence, that also epigenetic processes such as DNA and histone modifications, long non-coding RNAs and transcription factors orchestrate aberrant gene expression in heart failure. Among these epigenetic processes, N6-methyladenosine (m6A) is the most prevalent modification found in all classes of RNA. Such m6A patterns in for example mRNA can have influence on various mechanisms such as splicing, transport, storage or decay of mRNAs. Due to its reversible and dynamic nature regulated via methyltransferases (mainly the METTL3/METTL14/WTAP-complex) and demethylases (mainly FTO and ALkBH5) it adds a new layer of epigenetic regulation. Purpose: Changes in epigenetic processes are important mechanisms in heart failure progression. We aimed to elucidate the potential role of m6A methylation in heart failure development. Methods: We analysed m6A methylation in different stages of heart failure progression in mouse and human tissue via methylated RNA immunoprecipitation (meRIP) followed by next generation sequencing (NGS). With polysome fractionation followed by NGS, we studied a potential link between polysomal occupancy and m6a RNA methylation. Results: We found that approximately one quarter of all RNA transcripts in healthy mouse and human tissue carry m6A RNA methylation. During progression to heart failure we found that changes in m6A methylation exceed changes in gene expression in both, mouse and human. RNAs with altered m6A levels were mainly linked to metabolic and regulatory pathways, whereas changes in expression represented changes in structural plasticity. Furthermore, we found a link between m6A RNA methylation and altered RNA translation. Interestingly, transcripts with unchanged expression level but a differential change in their methylation level also showed differential polysomal occupancy. We could show a corresponding change in protein level, which points to a potential new mechanism of transcription-independent modulation of translation. The importance of m6A methylation was furthermore confirmed in a cardiomyocyte specific knock-out of the RNA demethylase FTO in mice where it lead to impaired cardiac function compared to control mice. Conclusions: We could show that the m6A landscape is altered in heart hypertrophy and heart failure. Methylation changes exceed expression changes in disease progression and lead to changes in protein abundance, which uncovers a new transcription-independent mechanism of translation regulation. Therefore, our data suggest that targeting epitranscriptomic mechansims, such as m6A methylation, might be a an interesting approach for thereapeutic interventions. Funding Acknowledgement: Type of funding source: Public grant(s) – EU funding. Main funding source(s): SFB 1002 Modulatory Units in Heart Failure